(untitled) (Revista de Artes Marciales Asiáticas, 2018)
Weight division is the most common way of categorizing athletes for competition in martial arts and combat sports. Eating disorders and the use of rapid weight loss methods are common among combat sports athletes, both at young and adult ages at all competition levels. Meanwhile, height is commonly regarded as determinant in kicking combat sports. The present study aimed to examine whether height categories can be used as a healthier alternative to weight categories for official competition. The height and weight of 153 male (n=80) and female (n=73) competitive taekwondo athletes aged between 10 and 16 were measured. Participants were classified by age, sex, and official weight category. Athletes were then sorted into ten hypothetical numbered height categories established in every age and sex group, according to World Health Organization (WHO) percentiles. There was a strong correlation between height and weight (r=0.843, p<0.01), and between height and weight categorization (r=0.681, p<0.01), and 68.18% of participants stayed the same, or moved only ±1 category by height from their original weight category. We conclude that young competitive taekwondo athletes can be categorized by height in official competition, as a healthier and more equitable alternative to the current weight divisions.